Philippine English Modules During Covid-19 Pandemic: Its Gender Sensitivity and Responsiveness - Aguilar-Delavin, Elreen (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The purpose of this research is to evaluate the manifestations of gender bias in DepEd Secondary English Modules. The distribution of characters and the occurrence of gender bias have been determined in self-learning modules (SLMs). In this research, both quantitative and qualitative methods of content analysis were used. These strategies were applied using the methodology given by Brugeilles and Cromer in their paper Analyzing Gender Representations in School Textbooks. The DepEd Region V English Self-Learning Modules for grades seven through ten were used in this research as part of the K-12 curriculum. It was discovered that there was a gender imbalance in secondary English SLMs along with pictures and text; females were underrepresented as men were represented twice in the modules; gender stereotyping was found to have the highest percentage of the four categories of the manifestations of gender bias, which is alarming to women who may feel that they have less value in society. The absence of women in occupations dominated by males demonstrates their inadequacy and dependence on men. The pedagogical implications of gender-responsive education must thus be emphasized, particularly in the new educational standard. It is advised that policies in Philippine schools be reexamined in order to determine their effectiveness.